Chlorophyll‐a in Antarctic Landfast Sea Ice: A First Synthesis of Historical Ice Core Data. Issue 11 (25th November 2018) - Meiners, K. M.; Vancoppenolle, M.; Carnat, G.; Castellani, G.; Delille, B.; Delille, D.; Dieckmann, G. S.; Flores, H.; Fripiat, F.; Grotti, M.; Lange, B. A.; Lannuzel, D.; et al.
Abstract: Historical sea ice core chlorophyll‐ a (Chl a ) data are used to describe the seasonal, regional, and vertical distribution of ice algal biomass in Antarctic landfast sea ice. The analyses are based on the Antarctic Fast Ice Algae Chlorophyll‐ a data set, a compilation of currently available sea ice Chl a data from landfast sea ice cores collected at circum‐Antarctic nearshore locations between 1970 and 2015. Ice cores were typically sampled from thermodynamically grown first‐year ice and have thin snow depths (mean = 0.052 ± 0.097 m). The data set comprises 888 ice cores, including 404 full vertical profile cores. Integrated ice algal Chl a biomass (range: <0.1–219.9 mg/m 2, median = 4.4 mg/m 2, interquartile range = 9.9 mg/m 2 ) peaks in late spring and shows elevated levels in autumn. The seasonal Chl a development is consistent with the current understanding of physical drivers of ice algal biomass, including the seasonal cycle of irradiance and surface temperatures driving landfast sea ice growth and melt. Landfast ice regions with reported platelet ice formation show maximum ice algal biomass. Ice algal communities in the lowermost third of the ice cores dominate integrated Chl a concentrations during most of the year, but internal and surface communities are important, particularly in winter. Through comparison of biomass estimates based on different sea ice sampling strategies, that is, analysis of full cores versus bottom‐ice section sampling, we identify biases in common sampling approaches and provide recommendations for future survey programs: for example, the need to sample fast ice over its entire thickness and to measure auxiliary physicochemical parameters. Plain Language Summary: Antarctic sea ice is a key driver of physical, chemical, and biological processes in the Southern Ocean. Importantly, sea ice serves as a substrate for microscopic algae which grow in the bottom, interior, and surface layers of the ice. These algae are considered an important food source for Antarctic marine food webs. Using a newly collated database of historical sea ice core chlorophyll‐ a data (a proxy for ice algal biomass) from coastal sites, we describe the seasonal and vertical variability of algal biomass in Antarctic landfast sea ice. The seasonal chlorophyll‐ a development is consistent with the current understanding of physical drivers of ice algal biomass, including the seasonal cycle of irradiance and surface temperatures driving landfast sea ice growth and melt. Our analyses show that algae in the lowermost third of ice cores drive the annual cycle of integrated biomass, but internal and surface communities are also important. Through comparison of biomass estimates based on different sea ice sampling strategies, that is, analysis of full cores versus bottom‐ice section sampling, we identify biases in common sampling approaches and provide recommendations for future survey programs: for example, the need to sample fast ice over its entire thickness and to measure auxiliary physical parameters, in particular snow‐thickness data. Key Points: First comprehensive collation of Antarctic landfast sea‐ice core chlorophyll‐ a data established Algae in lowermost third of ice cores drive annual cycle of integrated biomass, but internal and surface communities are also important Full‐profile ice‐core sampling and systematic collection of auxiliary physico‐chemical parameters is recommended for future studies